2006
DOI: 10.1007/s00442-006-0562-5
|View full text |Cite
|
Sign up to set email alerts
|

Is microbial community composition in boreal forest soils determined by pH, C-to-N ratio, the trees, or all three?

Abstract: In Fennoscandian boreal forests, soil pH and N supply generally increase downhill as a result of water transport of base cations and N, respectively. Simultaneously, forest productivity increases, the understory changes from ericaceous dwarf shrubs to tall herbs; in the soil, fungi decrease whereas bacteria increase. The composition of the soil microbial community is mainly thought to be controlled by the pH and C-to-N ratio of the substrate. However, the latter also determines the N supply to plants, the plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
335
10
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 625 publications
(391 citation statements)
references
References 38 publications
43
335
10
3
Order By: Relevance
“…This is different to a number of studies that identified soil pH as one of the main environmental factors driving soil microorganisms functions and structure (Bääth and Anderson 2003;Hackl et al, 2005;Högberg et al, 2007). However, the range of the pH values in our soils is very low (7.8-8.2) which is probably the main reason for the lack of the significant correlations.…”
Section: Discussioncontrasting
confidence: 99%
“…This is different to a number of studies that identified soil pH as one of the main environmental factors driving soil microorganisms functions and structure (Bääth and Anderson 2003;Hackl et al, 2005;Högberg et al, 2007). However, the range of the pH values in our soils is very low (7.8-8.2) which is probably the main reason for the lack of the significant correlations.…”
Section: Discussioncontrasting
confidence: 99%
“…Hogberg et al 50 have reported that the C/N ratio was as good as pH in predicting the soil microbial community. However, in this study the C/N ratio was increased somewhat artificially by the addition of C in the biochar, which was unavailable to microbes in a short incubation period, unlike the natural system investigated by Hogberg et al 50 Thus, in envfit test, C/N ratio was found to be significant in shaping the soil microbial community composition, which could be due to its high correlation with soil pH. Rape planting also showed some influence on the soil microbial community composition but only in treatments with biochar.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The immediate response of the ectomycorrhizal community to the N supply has been seen in several N-fertilization experiments and studies of N gradients and is widely accepted to be caused by a reduced supply of plant C to the fungal symbionts (e.g. Högberg et al 2007). Whereas the nutritional conditions for ectomycorrhizal species changed rapidly, the conditions for saprobic species probably changed during the course of the experiment by altered soil biogeochemistry as mentioned in the previous section.…”
Section: Response Of Saprobic Species To Fertilizationmentioning
confidence: 99%
“…Ectomycorrhizal fungi are directly dependent on the C supply from trees. When N availability in the soil is high, trees reduce C allocation to the roots and reduce investment of C in mycorrhizal fungi (Demoling et al 2008;Högberg et al 2007). However, there are few ectomycorrhizal species, such as Paxillus involutus and Lactarius rufus, and species of the Thelephoraceae and Corticiaceae which have been reported to remain unaffected, or even to increase their production of sporocarps in forest soils to which N has been added (Laiho 1970;Ohenoja 1978;Wästerlund 1982;Peter et al 2001a).…”
Section: Introductionmentioning
confidence: 99%